Augmented Reality for Mathematics Learning: A Study for Enhancing Mathematical Comprehension in High School Students - Yanuarto, Wanda Nugroho; Suanto, Elfis; Isnawan, Mohamad Galang (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
Numerous initiatives have sought to incorporate novel learning environments or technology, including Augmented Reality, into delivering more comprehensive education. But it's crucial to look at how this technology or settings impact different types of students. Research purposes: the main purposes of this study are the degree to which students are receptive to adopting augmented reality software as a learning tool and the effectiveness of such software in improving students' comprehension of probability and statistics in junior high school. Seventy-seventh graders from Purwokerto City, Indonesia's junior highs bordering urban and rural areas, participated. Research methods: two groups of students could be selected: one for the experiment and another for control purposes. In contrast to the control group, who stuck with tried-and-true teaching techniques, the experimental group conducted additional exploration of probability concepts either alone or in small groups using custom-built augmented reality software. While the control group continued to use more traditional methods of education, the experimental group utilised custom-built augmented reality software to explore probability concepts further, either individually or in small groups. All three courses met for a total of sixty-two days. Research results: The findings from the study showed that students' grasp of mathematical ideas can be improved by around 25.6% with the help of augmented reality learning apps. Furthermore, we analyse the differences in student learning and inquiry behaviours between two experimental conditions that differ in the complexity of augmented reality information. Furthermore, the results of the attitude questionnaire and the open-ended questions (5 items questions) corroborate the students' good opinions towards applications. However, in the future, researchers may look at how augmented reality affects students' more subjective characteristics, such as learning anxiety, and broaden the demographic of those who use these apps.